The Effect of Using A Teaching Strategy Based on Reading Picture in Text Comprehension for Basic Fourth Grade in Nablus Governorate - Hassoun, Asmaa Majid; Habayeb, Ali Hassan (Journal of Educational and Psychological Sciences, 2022)
This study aimed to find out the effect of using a teaching strategy based on reading picture in text comprehension for basic fourth grade students in Nablus governorate for the academic year 2020/2021. In order to achieve the objectives of the study, the researcher used a mixed approach that combines the quantitative and qualitative approaches using the test and the interview. Seven teachers of the fourth basic grade were interviewed in government schools in the governorate of Nablus, and a sample of fourth grade students from government schools in the governorate of Nablus was intentionally chosen. And their number reached (151) male and female students, as the experimental group consisted of (76) male and female students, and the control group of (75) male and female students, and a pre-achievement test was applied to them. The results of the study concluded that there was a statistically significant difference between the mean achievement scores of the experimental and control groups due to the teaching method, in favor of the experimental group. And the existence of a statistically significant difference between the mean achievement scores of the experimental group students, due to the type of measurement, in favor of the post-measurement. And there is a statistically significant difference between the achievement scores of the experimental and control groups due to the method variable, in favor of reading the picture, and there is no statistically significant difference between the mean achievement scores of the experimental and control groups due to a variable (gender, interaction between method and gender). In light of the results of the study, the researcher recommended that primary school teachers should be trained in the use of pictures and how to read them, and that the curriculum developers should take into account the simplicity and lack of complexity in the images, in addition to their clarity, and the need to train students to use pictures and read them correctly, and the need for more Local studies on the use of image reading strategy, its impact on the educational process, and its association with other variables.